Hybrid Chemoenzymatic Synthesis of C7‐Sugars for Molecular Evidence of in vivo Shikimate Pathway Inhibition. (23rd May 2022) - Rath, Pascal; Rapp, Johanna; Brilisauer, Klaus; Braun, Marvin; Kolukisaoglu, Üner; Forchhammer, Karl; Grond, Stephanie
Abstract: The design of distinctive chemical synthesis strategies aims for the most efficient routes towards versatile compounds in drug target studies. Here, we establish a powerful hybrid synthetic approach of total chemical and chemoenzymatic synthesis to efficiently obtain various 7‐deoxy‐sedoheptulose (7dSh, 1 ) analogues, unique C7 sugars, for structure‐activity relationship studies. 7dSh (1 ) is a rare microbial sugar with in planta herbicidal activity. As natural antimetabolite of 3‐dehydroquinate synthase (DHQS), 7dSh (1 ) inhibits the shikimate pathway, which is essential for the synthesis of aromatic amino acids in bacteria, fungi, and plants, but absent in mammals. As glyphosate, the most used chemical herbicide faces restrictions worldwide, DHQS has gained more attention as valid target of herbicides and antimicrobial agents. In vitro and in vivo analyses of the C7 ‐deoxysugars confirm DHQS as enzymatic target, highlight the crucial role of uptake for inhibition and add molecular aspects to target mechanism studies of C7 ‐sugars as our contribution to global efforts for alternative weed‐control strategies. Abstract : 7‐Deoxy‐sedoheptulose is a cyanobacterial antimetabolite of the 3‐dehydroquinate synthase, second enzyme of the shikimate pathway. Design of a hybrid synthesis of chemical and chemoenzymatic steps using heterologously expressed transketolase efficiently yielded the heptulose family. In vivo and in vitro studies on Anabaena variabilis and Arabidopsis thaliana gave a profound understanding of the mode of action.